Análisis Económico del Cultivo del Frijol (Phaseolus vulgaris L.) en Nicaragua, 1980 - 2014 - Solís Espinoza, Armando Josué; Vivas Viachica, Elgin Antonio Asesor (Managua (Nicaragua), 2017)
(En)
Ilus., Contiene CD con registro CD0007/18 y misma clasificación
Tesis (Lic. Agronegocios)